The Relationship of Meaning in Arabic Linguistic Studies - Arifa, Nabila; Rahmah, Sayyidatur (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study explores the semantics of Arabic, which has many lexical and grammatical meaning structures, with attention to semantic relationships such as tar?duf (synonymy, words with multiple meanings), isytir?k (polysemy, words with multiple meanings), and ta??dd (antonymy, opposite meanings), which are important for understanding the text of the Qur'an, literature, and religious communication. The main issue faced is the ambiguity in interpretation due to the lack of understanding of these relationship patterns in cultural contexts, which often leads to errors in interpretation or translation. The purpose of this study is to analyze how meaning relations work in deepening the understanding of Arabic linguistics both in theory and practice. The qualitative method used is based on a literature review with a descriptive-analytical approach to academic sources such as books, journals, and classical documents, resulting in the discovery of systematic patterns that emphasize the flexibility of language and beauty in rhetoric. Recommendations that can be conveyed from this study include the development of an Arabic language learning curriculum that focuses on contextual semantic analysis for teachers, translators, and students, in order to improve accuracy in interpreting sacred and contemporary texts.